The experience of maternal mental distress in The Gambia: A qualitative study identifying idioms of distress, perceptions of contributing factors and the supporting role of existing cultural practices. - Katie Rose M Sanfilippo; Bonnie McConnell; Buba Darboe; Hajara B Huma; Vivette Glover; Lauren Stewart (PLOS Global Public Health)
Maternal mental health problems are experienced frequently in the perinatal period and can be up to twice as common in women from low- and middle-income countries. The terms used to describe mental illness symptoms and the factors that contribute to developing these symptoms are affected by culture and context. Based on 14 focus group discussions held with pregnant women, health professionals and cultural leaders, this qualitative study aimed to understand women's experiences of mental distress during the perinatal period in The Gambia. To do this it aimed to 1) identify the most commonly used idioms of distress, 2) identify the factors believed to affect women's perinatal mental health and 3) explore the role of existing cultural practices, including musical practices, that were identified as locally significant in supporting maternal and mental health. Sondomoo tenkung baliyaa (Mandinka) and xel bu dalut (Wolof) were identified as the most commonly used idioms of distress which roughly translate to lack of a steady mind/heart. Using thematic analysis, six themes (Poverty of the healthcare system, Shifting cultural context, Economic factors, Social factors, Spiritual factors, and Cultural practices involving music) were identified to describe the factors that shape women's experience of mental health during the perinatal period. Lack of economic resources, the prevailing poverty of the health system, an unsupportive husband and spiritual attack by evil spirits or witches were common reasons given for a woman experiencing maternal mental distress. Various existing cultural practices involving music, such as fertility societies, naming ceremonies and community music-making, were recognised as valuable for supporting women's mental health during the perinatal period. This work emphasises that initiatives to support perinatal mental health should be grounded in an understanding of local community cultural practices, knowledge, and experiences.